Data Driven Comparison of Synthetic and Waste Based Bio-Geotextiles: A Systematic Literature Review - Lusi Dwi Putri; Muhammad Usman Tariq (International Journal of Artificial Intelligence Research, 2026)
Synthetic polymer geotextiles are widely used in geotechnical engineering for separation, reinforcement, drainage, and erosion control, but their production and end of life stages often raise environmental concerns due to fossil based raw materials and persistent plastic waste. In parallel, bio geotextiles manufactured from agricultural or agro industrial waste such as coir, jute, pineapple leaves, and other natural fibres have been promoted as a more sustainable alternative, although questions remain about their mechanical performance, durability, and long term serviceability. This study conducts a systematic literature review to compare manufactured synthetic geotextiles with waste based bio geotextiles, with a primary focus on coconut coir geotextiles produced from coconut husk waste. The comparison is framed from three perspectives, namely mechanical and hydraulic performance, durability and degradation behaviour, and environmental sustainability including life cycle impacts. Scientific databases were searched using predefined keywords and inclusion criteria, resulting in a final sample of 20 core journal articles published between 2011 and 2025, most of which investigate coir based products for slope stabilization, erosion control, and low volume road applications. The findings show that coir bio geotextiles can provide comparable short term reinforcement and erosion control to conventional products in low to medium demand applications, particularly for slope stabilization and surface erosion control, although synthetic geotextiles still outperform in high load and long term applications. From an environmental perspective, coir geotextiles and other bio based products generally offer lower embodied energy and greenhouse gas emissions, but this advantage depends on local supply chains, fibre processing, and replacement frequency. The novelty of this review lies in integrating geotechnical performance evidence with environmental assessment results and highlighting how simple data driven metrics can support material selection for coir based bio geotextiles. The study concludes with a set of research gaps and design recommendations that bridge geotechnical engineering and sustainable materials science.